2016
DOI: 10.3390/ijms17101760
|View full text |Cite
|
Sign up to set email alerts
|

Towards Stratified Medicine in Plasma Cell Myeloma

Abstract: Plasma cell myeloma is a clinically heterogeneous malignancy accounting for approximately one to 2% of newly diagnosed cases of cancer worldwide. Treatment options, in addition to long-established cytotoxic drugs, include autologous stem cell transplant, immune modulators, proteasome inhibitors and monoclonal antibodies, plus further targeted therapies currently in clinical trials. Whilst treatment decisions are mostly based on a patient’s age, fitness, including the presence of co-morbidities, and tumour burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Given the number of agents now approved for the treatment of RRMM, treatment decisions are becoming increasingly complex [ 7 , 21 24 ]. While the choice of treatment regimen at relapse typically takes account of patient, disease and treatment characteristics (e.g., performance status, comorbidities, tumor burden, cytogenetics, previous treatment responses and toxicities), there is no validated strategy for the identification of patients who are likely to respond well to a given treatment at relapse [ 23 , 25 28 ]. Factors such as cytogenetics, serum albumin, serum lactate dehydrogenase (LDH) and β2-microglobulin are established prognostic variables in patients with newly diagnosed MM; however, the role of these factors in predicting prognosis in RRMM has been less well studied [ 25 – 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the number of agents now approved for the treatment of RRMM, treatment decisions are becoming increasingly complex [ 7 , 21 24 ]. While the choice of treatment regimen at relapse typically takes account of patient, disease and treatment characteristics (e.g., performance status, comorbidities, tumor burden, cytogenetics, previous treatment responses and toxicities), there is no validated strategy for the identification of patients who are likely to respond well to a given treatment at relapse [ 23 , 25 28 ]. Factors such as cytogenetics, serum albumin, serum lactate dehydrogenase (LDH) and β2-microglobulin are established prognostic variables in patients with newly diagnosed MM; however, the role of these factors in predicting prognosis in RRMM has been less well studied [ 25 – 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the choice of treatment regimen at relapse typically takes account of patient, disease and treatment characteristics (e.g., performance status, comorbidities, tumor burden, cytogenetics, previous treatment responses and toxicities), there is no validated strategy for the identification of patients who are likely to respond well to a given treatment at relapse [ 23 , 25 28 ]. Factors such as cytogenetics, serum albumin, serum lactate dehydrogenase (LDH) and β2-microglobulin are established prognostic variables in patients with newly diagnosed MM; however, the role of these factors in predicting prognosis in RRMM has been less well studied [ 25 – 32 ]. Recently, a risk stratification algorithm has been developed to help physicians predict survival outcomes in patients starting second-line treatment, which incorporates 16 predictors relating to patient frailty and disease aggressiveness at diagnosis and following first-line treatment [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…B Gene interaction network of CYP2D6, the target gene of rs1800716 variant with the other genes. Mined references underpinning the literature-mining network of rs1800716 is presented in Supplementary 8 has been suggested that PTPRC, as an adhesion molecule, is involved in the spread of the tumour and immortalisation of the tumour cells during malignancy [52]. In gastric cancer, it has been shown that CTSF is involved in the growth and apoptosis where CTSF knockdown promotes proliferation by inhibiting apoptosis [53].…”
Section: Discussionmentioning
confidence: 99%
“…They found that inhibition of miR-21 significantly impaired cell viability and blocked clonogenic growth of MM cells in stroma-free conditions [24]. Reportedly, expression of some miRNAs, including miR-223, miR-16, miR-519d, and miR-485-5p were found highly expressed in MM-BMSCs compared to normal counterparts [25]. In addition, it was confirmed that upregulation of miR-29b in the bone marrow microenvironment can impair osteoclast differentiation and impede osteoclast activation induced by MM cells [26].…”
Section: Involvement Of Mirna In the Bone Marrow Microenvironmentmentioning
confidence: 99%